2016
DOI: 10.1051/matecconf/20178802002
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterizations of Composite Material Based on Carbon Fiber and Two Thermoset Resins

Abstract: Abstract.In the present investigation, we used two types of thermoset resins (epoxy resin and phenol formaldehyde resin) with carbon fiber (CF) to produce composite materials. CF/epoxy resin composite and CF/phenolformaldhyde resin composite were fabricated and compared between their mechanical properties as compression, tension and flexural. it was found that mechanical properties of CF/epoxy composite higher than mechanical properties of CF/phenolformaldhyde resin composite such as flexural strength of CF/ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…By comparing the performance parameters of typical thermosetting resins in Table 2 , it is found that the epoxy resin has good comprehensive properties, especially the mechanical properties of the structure can be improved with small bending strain. Also, given that epoxy resin has good combination with reinforced carbon fibers, which is conducive to improving the interfacial properties of the composite [ 40 ]. Therefore, this article selects epoxy resin 5208 as the matrix material for composite floor structure design.…”
Section: Selection Of Raw Materials For Composite Floormentioning
confidence: 99%
“…By comparing the performance parameters of typical thermosetting resins in Table 2 , it is found that the epoxy resin has good comprehensive properties, especially the mechanical properties of the structure can be improved with small bending strain. Also, given that epoxy resin has good combination with reinforced carbon fibers, which is conducive to improving the interfacial properties of the composite [ 40 ]. Therefore, this article selects epoxy resin 5208 as the matrix material for composite floor structure design.…”
Section: Selection Of Raw Materials For Composite Floormentioning
confidence: 99%
“…Muralidhara et al [5] researched on the mechanical properties of carbon fiber/epoxy composites under three dissimilar fiber architecture (T800CF/Ep,T700CF/Ep, T300CF/Ep) thereby concluding that tensile and flexural properties are improved in T800CF/Ep composite when compared to other composition. Fouda et al [6] studied the mechanical properties of carbon fiber reinforced with epoxy composites because the more adhesion bond of the resin matrix. Carbon fiber reinforced polymer composites are superior compared to the metals and other polymers when used during spring applications [7].…”
Section: Introductionmentioning
confidence: 99%